Direktive dynamisk-lokative sætningsemner: Opbygning, betydning og modificering - Westergaard, Lennart (Journal of Language Works - Sprogvidenskabeligt Studentertidsskrift, 2019)
The paper gives an account of a subtype of Danish non-finite constructions that express a theme argument’s movement towards a goal. They are termed ‘directive dynamic-locative non-finite predications’. The structural analysis shows that the construction has two variants: 1. a non-agentive variant with two arguments: a theme and a locative goal; and 2. a causative variant with three arguments, i.e. additionally an agentive argument. In both cases an adverb functions as the head of the construction. In the previous literature, it has been argued that the construction codes for mood, distinguishing between directives and non-directives realized as a topological paradigm (Hansen & Heltoft 2011). However, I show that the variants are not formally distinguished. Both variants are, though, in complementary distribution, with the prototypical directive variant only occurring with present time reference and the narrative variant only occurring with past time reference. The directive and the narrative variant are analysed as polysemous and resemble historical imperatives. Based on the co-occurrence of clausal adverbials with the construction, it is argued that a structural analysis (in terms of categorical dependency to finiteness) of these in Danish should be reconsidered. An analysis solely based on their semantic scope with regard to the model of the layered clause structure seems more fruitful.